Bombesin affects the central nervous system to produce sodium intake inhibition in rats - DeCaro, G.; Polidori, C.; Menani, José Vanderlei [UNESP]; Johnson, A. K. (Elsevier B.V., 1997)
Bombesin (BN) elicits in the rat important behavioural modifications, including inhibition of food and of water intake. Recently, it has been observed that the peptide also inhibits the intake of sodium chloride. To stare whether BN possesses a selective antinatriorexic effect or it elicits only an aspecific depression of ingestive behaviour, we studied the effects of this peptide on the intake of sodium, water or sucrose of Wistar rats after injections into the fourth brain ventricle or into selected brain areas involved in the control of sodium intake, containing BN-like peptides and/or their precursors or specific receptors. We observed that: a) BN (100-200 ng/rat) injected into the fourth brain ventricle inhibits not only the intake of 2% NaCl of sodium depleted rats but also that of water and of 5% sucrose; b) BN (5-50 ng/rat) administered into the nucleus of the solitary tract and the medial amygdala does not influence the intake of these fluids and c) BN (5-50 ng/rat) injected into the paraventricular nucleus does not influence the intake of water and 5% sucrose but potently inhibits that of 2% NaCl. We concluded that the inhibitory effect elicited on salt intake by intracranial administration of BN is selective for this behaviour and is not the expression of an aspecific depression of ingestive behaviour. (C) 1998 Elsevier B.V.
Keywords: bombesin; sodium appetite; nucleus of the solitary tract; medial amygdala; paraventricular nucleus